2012
DOI: 10.1095/biolreprod.111.097261
|View full text |Cite
|
Sign up to set email alerts
|

Timing Sexual Differentiation: Full Functional Sex Reversal Achieved Through Silencing of a Single Insulin-Like Gene in the Prawn, Macrobrachium rosenbergii1

Abstract: In Crustacea, an early evolutionary group (∼50 000 species) inhabiting most ecological niches, sex differentiation is regulated by a male-specific androgenic gland (AG). The identification of AG-specific insulin-like factors (IAGs) and genomic sex markers offers an opportunity for a deeper understanding of the sexual differentiation mechanism in crustaceans and other arthropods. Here, we report, to our knowledge, the first full and functional sex reversal of male freshwater prawns (Macrobrachium rosenbergii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
152
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(156 citation statements)
references
References 20 publications
4
152
0
Order By: Relevance
“…qRT-PCR showed that IAG was present at low levels in the hepatopancreas, similar to results from C. sapidus (Chung et al, 2011) and F. chinensis (Ventura et al, 2012). However, this result also differed from a previous report (Ma et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…qRT-PCR showed that IAG was present at low levels in the hepatopancreas, similar to results from C. sapidus (Chung et al, 2011) and F. chinensis (Ventura et al, 2012). However, this result also differed from a previous report (Ma et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…The reduced growth of Mr-IAG-silenced individuals implied that Mr-IAG may act as a growth regulator (Ventura et al, 2009). Further study has shown that the IAG gene is closely related to metabolism in M. rosenbergii (Ventura et al, 2012). IAG may, thus, represent an excellent positional and functional candidate gene for growth traits in crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanism controlling sex maturation, a high-quality normalized cDNA library from testis tissue of this species has been established (Qiao et al, 2012). For this reason, molecular mechanisms regulating the expression of sex-specific and sex-determining genes in crustaceans have received great attention in recent years Kato et al, 2011;Ventura et al, 2012). In the present study, we aimed to obtain a full cDNA clone encoding the Sxl gene from the cDNA library of testis in M. nipponense, and to examine the expression pattern of the Sxl gene during the embryonic development, larvae, and post-larvae stages of M. nipponense.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vivo silencing of Cq-M15 was lethal, suggesting it has a vital function during the molt cycle. While numerous gene- silencing studies assessing the functionality of novel crustacean genes have been published previously (Ventura et al, 2009(Ventura et al, , 2012Rosen et al, 2010), to the best of our knowledge, the lethal effect of gene silencing has been previously reported in crustaceans only once (Christoffersen et al, 1989). We had shown earlier that silencing of particular transcripts in C. quadricarinatus affects the formation of the extracellular matrix and the calcification process (Shechter et al, 2008b;Glazer et al, 2010), as well as the duration of molt cycles (Pamuru et al, 2012;Tynyakov et al, 2015).…”
Section: Discussionmentioning
confidence: 90%